WAYS TO IMPROVE THE REGISTRATION OF MEDICINES AT PHARMACEUTICAL ENTERPRISES - DATSENKO, GANNA; KUDYRKO, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the need for accounting of medicines in the process of pharmaceutical companies, as well as ways to improve accounting, because medicines and medical equipment are widely used by the entire population of Ukraine. As this type of goods is quite specific, companies must properly maintain accounting records, as well as timely submit various types of reports to regulatory authorities. To do this, you need to be able to properly maintain current records of operations related to drugs and medical equipment sold in pharmacy networks.In this regard, the typical correspondence of accounts used for the production, purchase, domestic movement and sale of medicines and medical supplies is considered. The scheme of the organization of activity of the pharmaceutical enterprises for improvement of accounting of the goods which belong to the specified specific link is resulted. Ways to improve the accounting of pharmaceutical products have been identified, which will lead to the modernization of the process of procurement and sale of medicines and medical supplies. Several types of internal documents are proposed, the use of which will help facilitate the accounting of medicines and their reporting. Improving the accounting of medicines will lead to the timeliness of purchases of goods that are in short supply and reduce the purchase of those goods that are not in demand. A prerequisite for improving the accounting of medicines is the use of the latest technologies, the development and implementation of modern software, as well as the training of staff who will perform the duties of an accountant.All the areas proposed in the article to improve the accounting of medicines and medical equipment will help in the process of pharmacy to facilitate the work of the accountant, conduct an inventory of goods and conduct internal audits of transactions related to purchase, internal movement and sale of goods.
Keywords: accounting; medicines; medical equipment; pharmaceutical company; accounting accounts; stocks; primary documents; reporting; purchase of goods; sales